A Combined Study on Optimization, In Silico Modeling, and Genetic Modification of Large Scale Microbial Cellulase Production. (21st December 2022) - Rabby, Md. Raisul Islam; Ahmed, Zabed Bin; Paul, Gobindo Kumar; Chowdhury, Nafisa Nusrat; Akter, Fatema; Razu, Mamudul Hasan; Karmaker, Pranab; Khan, Mala
Abstract : Cellulase is a biocatalyst that hydrolyzes cellulosic biomass and is considered a major group of industrial enzymes for its applications. Extensive work has been done on microbial cellulase but fungi are considered a novel strain for their maximum cellulase production. Production cost and novel microbial strains are major challenges for its improvement where cheap agro wastes can be essential sources of cellulose as substrates. The researcher searches for more cellulolytic microbes from natural sources but the production level of isolated strains is comparatively low. So genetic modification or mutation can be employed for large-scale cellulase production before optimization. After genetic modification than in silico molecular modeling can be evaluated for substrate molecule's binding affinity. In this review, we focus not only on the conventional methods of cellulase production but also on modern biotechnological approaches applied to cellulase production by a sequential study on common cellulase-producing microbes, modified microbes, culture media, carbon sources, substrate pretreatment process, and the importance of optimum pH and temperature on fermentation. In this review, we also compare different cellulase activity determination methods. As a result, this review provides insights into the interrelationship between the characteristics of optimizing different culture conditions, genetic modification, and in silico enzyme modeling for the production of cellulase enzymes, which may aid in the advancement of large-scale integrated enzyme manufacturing of substrate-specific enzymes.